DETERMINANTS OF EXCLUSIVE BREAST MILK IN RURAL COMMUNITIES - Naya Erna Wati; Fitriana Kurniasari Solikhah; Eka Wulandari (Indonesian Journal of Health Care Management, 2022)
Introduction:  Exclusive breastfeeding is the process of feeding infants in the form of breast milk alone without other additional foods until the baby is 6 months old. Objective: The purpose of this study was to identify the determinants of exclusive breastfeeding practices. Methods: The design of this research is a cross sectional study. Purposive Sampling 125 mothers with child aged < 24 months. Data were collected between June and August 2022. Statistical analysis using chi square test, multivariate logistic regression was used to identify the determinants of the success of exclusive breastfeeding. Results: Determinants of exclusive breastfeeding are enabling factors use of health services (p value = 0.000; Exp.B = 2, 207); reinforcing factors : husband's support (p value = 0.001, Exp (B) = 7,800); and  the role of health workers (p value = 0.002, Exp (B) = 11.833). Conclusion: There is a relationship between  enabling factors and reinforcing factors with exclusive breastfeeding in rural communities. It is necessary to immediately implement and enforce a joint policy between the government, health workers, empowering family support by increasing awareness and creating a supportive environment for the success of exclusive breastfeeding.